An amygdala-to-cingulate cortex circuit for conflicting choices in chronic pain - Kristina Valentinova; Mario A. Acuña; Niels R. Ntamati; Natalie E. Nevian; Thomas Nevian (Cell Reports, 2023)
Summary: Chronic pain is a complex experience with multifaceted behavioral manifestations, often leading to pain avoidance at the expense of reward approach. How pain facilitates avoidance in situations with mixed outcomes is unknown. The anterior cingulate cortex (ACC) plays a key role in pain processing and in value-based decision-making. Distinct ACC inputs inform about the sensory and emotional quality of pain. However, whether specific ACC circuits underlie pathological conflict assessment in pain remains underexplored. Here, we demonstrate that mice with chronic pain favor cold avoidance rather than reward approach in a conflicting task. This occurs along with selective strengthening of basolateral amygdala inputs onto ACC layer 2/3 pyramidal neurons. The amygdala-cingulate projection is necessary and sufficient for the conflicting cold avoidance. Further, low-frequency stimulation of this pathway restores AMPA receptor function and reduces avoidance in pain mice. Our findings provide insights into the circuits and mechanisms underlying cognitive aspects of pain and offer potential targets for treatment.